Upaya Meningkatkan Kinerja Organisasi dengan Model Blue Ocean Leadership melalui Dimensi Spiritual - Wahyu Eko Pujianto; Ayu Lucy Larassaty (Journal of Research and Technology, 2022)
The purpose of the research is to increase the performance of the company through the blue ocean leadership and spiritual dimension. This research methods uses a quantitative approach. The population in this research was milenial generation employees who work for more than two years in Sidoarjo, there was 19.818 people. This research applied purposive sampling with number of 391 respondents and the data collection was provided through googledoc. The analysis in this research applied Partial Least Square (PLS) by using smartPLS 3.0 software. There were two specifications of the model used for PLS: outer and inner model. The result of this research found that blue ocean leadership have significant impact on spiritual dimension and organisational performance, and spiritual dimension have significant impact on organisational performance.